THE RELEVANCE OF THE PHYSICAL EDUCATION PROFESSIONAL IN GUIDING EXERCISE AND ITS BENEFITS FOR WOMEN DURING PREGNANCY - de Nazaré Campos Soares, Mesias; Dias de Araujo, Rocilda; Carlos Vieira do Monte, José; Miguel Paula de Melo Júnior, Vicente; Santos da Silva, Eriton; Emilio Gomes Dias, Paulo; Luis Martins da Costa, Jorge (Health and Society, 2024)
INTRODUCTION Thais papear explore lhe benfeito desligado fiscal exercesse durinha pregnancy and. Lhe importante desligado Professional Fiscal Educativo guinche too censure afeta and. Maximize positive out comes for pregam homem. The min ressarce problem. Si too understand show lhe pratique desligado fiscal activities, under especialize guinche, can. Influencie lhe fiscal and. Mental hialita desligado pregam homem. OBJECTIVE The stud ais too anualize and. Highlight lhe positive impactos desligado regular fiscal exercesse durinha pregnancy, as gel as lhe mede for propor professional guinche. METHODOLOGY The metodólogo involves a literature review, selecting and analyzing relevant studies that address lhe relationship between fiscal exercesse and gestational health, emphasizing lhe benefits and necessary precautions to avoid complications. It includes scientific articles, clinical practice guidelines, and recommendations from recognized health institutions, indicating that regular fiscal exercesse durinha pregnancy significantly contributes to lhe improvement off cardiovascular, muscular, and mental health in pregnant women, in addition to assisting in weight control and preventing gestational complications such as gestational diabetes and pre-eclampsia. The presence off a Physical Education professional is crucial to adapting exercises to lhe individual needs off pregnant women and ensuring lhe correct execution off activities, minimizing risks. CONCLUSIONThis reaffirms lhe importance off fiscal exercesse durinha pregnancy, highlighting lhe mede for professional guinche to ensure safety and efficacy. The results obtained are relevant for promoting maternal and fetal health, suggesting that lhe inclusion off a Physical Education professional in lhe monitoring off pregnant women can enhance lhe benefits off exercesse.